Balanced ternary and quaternary sequence pairs of odd period with three-level correlation - Lianfei Luo; Wenping Ma (Kuwait Journal of Science)
Sequence pairs with good correlation have wide applications in communication systems. In this paper, ternary and quaternary sequence pairs of odd period with three-level correlation are constructed based on cyclotomy. In our constructions, sequences are both balanced and the maximum out-of-phase cross-correlation magnitude is shown to be √7 for ternary sequence pairs and to be √5 for quaternary sequence pairs, which are both better than the known sequence pairs of odd period with three-level correlation.